1998
DOI: 10.1074/jbc.273.42.27213
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Cytokine Receptor Antagonist Directly Targeting gp130

Abstract: The interleukin-6-type family of cytokines bind to receptor complexes that share gp130 as a common signaltransducing subunit. So far, receptor antagonists for interleukin-6-type cytokines have been constructed that still bind to the specific ligand binding subunit of the receptor complex, but have lost the ability to stimulate gp130. Such receptor antagonists compete for a specific receptor of a member of the cytokine family. Interleukin-6 only binds to gp130 when complexed with the interleukin-6 receptor that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…This is essentially the same mechanism of action that has been observed for IL-6/IL-6R signaling. Oncostatin M differs from IL-11 and IL-6 in that it directly binds to gp130 and signals through either gp130/leukemiainhibitory factor receptor ␤ or gp130/oncostatin M receptor heterodimers (51,52). Because gp130 is ubiquitously expressed, the FIGURE 10.…”
Section: Discussionmentioning
confidence: 99%
“…This is essentially the same mechanism of action that has been observed for IL-6/IL-6R signaling. Oncostatin M differs from IL-11 and IL-6 in that it directly binds to gp130 and signals through either gp130/leukemiainhibitory factor receptor ␤ or gp130/oncostatin M receptor heterodimers (51,52). Because gp130 is ubiquitously expressed, the FIGURE 10.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased levels of IL 6 (and in this case, also TNF-alpha and CRP) are associated with senile osteoporosis in both females and males (217). This may offer a possibility for pharmacological intervention by IL 6R blockade (218). Even for IL 6, however, not all investigators have found elevated serum levels in perfectly healthy elderly humans (219).…”
Section: Cytokine Production and Responsementioning
confidence: 99%
“…COS-7 cells were transiently transfected with p409-vIL-6 using the DEAE-dextran method (42,64). The next day, DMEM containing 10% FCS was changed to 5 ml FCS-free DMEM.…”
Section: Methodsmentioning
confidence: 99%